2019
DOI: 10.3390/en12183453
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Power Source Performance Decrease in a PV/WT/FC Hybrid Power Generation System on the Result of a Multi-Criteria Analysis of Load Distribution

Abstract: The article presents a mathematical model designed for scheduling cooperation between Hybrid Power Generation System HPGS and an electricity system viewed from a multifaceted perspective. The multifaceted approach consists in taking into account energy, economic, and environmental criteria in the calculation process. The considered HPGS is constructed of a photovoltaic installation PV, wind turbines WT, and energy storage in the form of an electrolyzer El coupled with a fuel cell FC. The model consists of ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The results showed that a chattering reduction of 84% could be achieved using the proposed technique. Ceran and Orłowska [28] investigated the decline of power source performance in a hybrid power system based on a multi-criterion analysis of load distribution. The authors introduced a mathematical model intended for planning cooperation in a hybrid power system consisting of photovoltaic panels, wind turbines, and a discrete regenerative fuel cell.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that a chattering reduction of 84% could be achieved using the proposed technique. Ceran and Orłowska [28] investigated the decline of power source performance in a hybrid power system based on a multi-criterion analysis of load distribution. The authors introduced a mathematical model intended for planning cooperation in a hybrid power system consisting of photovoltaic panels, wind turbines, and a discrete regenerative fuel cell.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The modelling techniques of hybrid systems presented in the above mentioned works do not take into account the decrease in stack efficiency after years of operation. Consequently, in such a hybrid system, energy imbalance may occur [24], which will result in increased consumption from the power grid [9].…”
Section: Introductionmentioning
confidence: 99%
“…The newly-developed testbed allows achieving the parameters used in similar research (ball speed and the impact force) [11]. Most studies simulate the effects of hail using pneumatic equipment that provides the energy needed to move a piece of ice [2,4,[32][33][34][35][36]. The hail test requires expensive, time-consuming equipment.…”
Section: Introductionmentioning
confidence: 99%